Solute transporters and aquaporins are impaired in celiac disease - Laforenza, Umberto; Miceli, Emanuela; Gastaldi, Giulia; Scaffino, Manuela F.; Ventura, Ulderico; Fontana, Jacopo M.; Orsenigo, Maria N.; Corazza, Gino R. (Biology of the cell, 2010)
Background information. Celiac disease is a chronic inflammatory disorder of the small bowel induced in genetically susceptible subjects by gluten ingestion. Diarrhoea, weight loss and malabsorption represent the major clinical presentation of the disease. Here we examined the possible alteration in the expression and localization of water channels [AQPs (aquaporins)] and some solute transporters in duodenal mucosa of celiac disease patients. Duodenal biopsies from untreated celiacs, treated celiacs, healthy controls and disease controls were considered in the present study. The expressions of some AQPs and transporter mRNAs in human duodenal biopsies were determined by semi‐quantitative RT—PCR (reverse transcription PCR) and real‐time RT—PCR. The localization of AQPs 3, 7 and 10 and of SGLT1 (Na+/glucose co‐transporter 1), PEPT1 (H+/oligopeptide transporter 1) and NHE3 (Na+/H+ exchanger 3) was evaluated by immunohistochemistry. Results. AQPs 3, 7, 10 and 11, SGLT, PEPT and NHE, CFTR (cystic fibrosis transmembrane conductance regulator) and NKCC (Na‐K‐2Cl co‐transporter) mRNAs were expressed in duodenal biopsies of healthy controls, treated celiac patients and disease controls. The expression of transcripts was virtually absent in duodenal biopsies of untreated celiac disease patients except for CFTR and NKCC. In healthy controls, immunohistochemistry revealed a labelling in the apical membrane of surface epithelial cells of the duodenum. The immunolabelling was heavily reduced or absent in untreated celiac patients, while it was normal in patients consuming a gluten‐free diet for at least 12 months. Conclusions. Our results indicate that the main routes for water and solute absorption are deficient in celiac disease and may play a role in the onset of malabsorption symptoms.